Trends in Concomitant Meniscal Surgery Among Pediatric Patients Undergoing ACL Reconstruction: An Analysis of ABOS Part II Candidates From 2000 to 2016. Issue 9 (24th September 2019) - Cruz, Aristides I.; Gao, Burke; Ganley, Theodore J.; Pennock, Andrew T.; Shea, Kevin G.; Beck, Jennifer J.; Ellis, Henry B.
Background: Rates of anterior cruciate ligament (ACL) reconstruction among pediatric and adolescent patients are increasing. Limited knowledge exists about population-level rates of concomitant meniscal surgery in this age group. Purpose/Hypothesis: This study sought to examine trends in concomitant meniscal procedures and describe short-term complications in pediatric and adolescent patients undergoing ACL reconstruction. We hypothesized that overall meniscal surgery rates are increasing and that the likelihood of performing meniscal repair or meniscectomy is associated with patient- and surgeon-specific factors. Study Design: Cross-sectional study. Methods: We queried ACL procedures in patients younger than 19 years reported by American Board of Orthopaedic Surgery (ABOS) part II examination candidates from 2000 to 2016. Regression models examined associations between patient and surgeon characteristics, year of surgery, follow-up time, meniscal procedure type, and number and type of complications. Results: A total of 9766 cases were identified. Females represented 46% (n = 4468) of included cases. Mean patient age was 16.1 years (SD, 1.62 years; range, 0-18 years). The rate of concomitant ACL-meniscal procedures increased from the years 2000 to 2016 (49%-60%; P = .005). Surgeons with sports medicine (+7.0%) or pediatric orthopaedic fellowship (+6.6%) training had a higher likelihood of reporting a concomitant ACL-meniscal procedure ( P = .003 and .006, respectively). Sports medicine–trained surgeons were more likely to perform meniscal repair compared with meniscectomy (+3.0%; P = .016). Younger patient age was associated with increased likelihood of undergoing meniscal repair compared with meniscectomy. Overall reported complication rate was 12.8%. Notable reported complications included infection (1.61%), arthrofibrosis (1.14%), and deep venous thrombosis or pulmonary embolism (0.11%). Sports medicine and pediatric orthopaedic fellowship training was associated with higher rates of reporting postoperative stiffness and/or arthrofibrosis. Conclusion: Among ABOS part II candidates, concomitant ACL-meniscal surgery has become more common than isolated ACL procedures. Procedures involving sports medicine fellowship–trained surgeons and younger patients were associated with increased rates of meniscal repair compared with meniscectomy. Pediatric orthopaedic and sports medicine training was associated with a greater likelihood of being involved in a concomitant ACL-meniscal procedure of any kind, and surgeons with such training also reported a higher incidence of postoperative stiffness and/or arthrofibrosis in patients.